Em tempos de crise, novos ajustes: uma análise sobre a reforma do benefício de pensão por morte - Leite, Ana Adrielle Bertini Pinto de Castro (Universidade Federal Rural do Semi-Árido, 2017)
The present study dealt with the social security benefit of death pension and the main alterations suffered by this benefit, in particular, regarding Law no. 13.135 / 2015, which amended important articles of Law no. 8.213 / 91, such as those dealing with the duration of the benefit and the contribution time required to qualify for such benefit. Thus, for a better understanding of the subject, the concept and legislative path of the death benefit in Brazil were presented, which includes the alterations suffered by this benefit, and after that the reasons given by the government for the Laws changes were presented, including the reasons presented for PEC 287/2016, which may also change the death pension. In addition, a criticism was made as to the governmental reasons given, paying special attention to the supposed problem of the social security deficit and the constant use of this justification in times of political-economic crises of the country to legally limit hard-won social rights. Finally, a critical analysis was carried out regarding the need to publish Law no. 13.135 / 2015 and the impacts caused by said law, using data on the age of beneficiaries, the amount of benefits granted and active in 2015.
Monografia
Keywords: Previdência social; Pensão por morte; Lei n. 13.135/2015; Crise; Déficit previdenciário; Social security; Death pension; Changes; Law no. 13,135 / 2015; Crisis; Deficit; CIENCIAS SOCIAIS APLICADAS::DIREITO